2006
DOI: 10.1158/0008-5472.can-06-3329
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of RET Receptor–Mediated Oncogenesis in Multiple Endocrine Neoplasia 2B

Abstract: Multiple endocrine neoplasia 2B (MEN 2B) is an inherited syndrome of early onset endocrine tumors and developmental anomalies. The disease is caused primarily by a methionine to threonine substitution of residue 918 in the kinase domain of the RET receptor (2B-RET); however, the molecular mechanisms that lead to the disease phenotype are unclear. In this study, we show that the M918T mutation causes a 10-fold increase in ATP binding affinity and leads to a more stable receptor-ATP complex, relative to the wild… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(93 citation statements)
references
References 43 publications
4
86
0
3
Order By: Relevance
“…We have recently suggested that a quantitative increase in RET kinase activity may be responsible for the greater phenotypic severity of MEN 2B (RET M918T) relative to other MEN 2 mutants (13). Further, we have recently shown that MEN 2A and 2B up-regulate a similar compliment of genes; however, the more aggressive MEN 2B form induces a higher level of expression of these genes due to its increased kinase activity (36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have recently suggested that a quantitative increase in RET kinase activity may be responsible for the greater phenotypic severity of MEN 2B (RET M918T) relative to other MEN 2 mutants (13). Further, we have recently shown that MEN 2A and 2B up-regulate a similar compliment of genes; however, the more aggressive MEN 2B form induces a higher level of expression of these genes due to its increased kinase activity (36).…”
Section: Resultsmentioning
confidence: 99%
“…Immunoprecipitation and immunoblotting were done according to previously published methods (13). Briefly, lysed cells were separated into cytosolic and membrane-associated fractions by centrifugation at 12,000 Â g. Cytosolic fractions were immunoprecipitated with 0.8 Ag antibody and 20 AL protein A/G slurry (Santa Cruz Biotechnology).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a case of familial phaeochromocytoma described in 1886 was shown to result from a germline RET mutation 121 years later (9). MEN2 is an autosomal dominantly inherited disorder and is divided into three clinical subtypes, two of which (MEN2A and MEN2B) are characterised by the development of medullary thyroid cancer (MTC) and (10)(11)(12). Individuals with MEN2A have about a 50% risk of developing aPCA but the mean age at diagnosis of MTC is earlier than that of aPCA (w40 years) and so, compared with individuals with germline SDHB, SDHD or VHL mutations, individuals with MEN2 are less likely to present with sporadic non-syndromic phaeochromocytoma.…”
Section: Retmentioning
confidence: 99%
“…RET M918T, which is also the most frequent somatic mutation in sporadic MTCs is prognostic of aggressive disease thus indicating a strong carcinogenic potential [3,7]. Substitution of methionine 918 with threonine results in increased Ret kinase activity, release of auto-inhibition, increased ligandindependent formation of activated monomers and dimers, and change in substrate specificity contributing to the receptor oncogenic activity [8,9]. Preclinical studies have provided evidence that Ret oncoproteins may represent a therapeutic target exploitable in subsets of thyroid tumors [5,10,11].…”
Section: Introductionmentioning
confidence: 99%